2020
DOI: 10.1089/whr.2019.0027
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Trauma, Violence, and Stress on Sexual Health Outcomes Among Female Clinic Clients in a Small Northeastern U.S. Urban Center

Abstract: Background: Threats to sexual health can emerge across one's life span and are influenced by individual and interpersonal experiences, as well as certain environmental exposures. Although previous research has recognized the importance of ecological frameworks to understand the complexity of health and behaviors in marginalized communities, there continues to be a dearth of research that truly utilizes this perspective to gain insight into the multifaceted factors that can concurrently influence threats to sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Women who have trauma history are over twice as likely to have multiple sex partners, perceive peer norms for risky sex, have lower communication frequency with partners about sexual boundaries, and have lower self-efficacy for refusing sex. This study adds to the literature showing that having a history of trauma may be associated with greater adverse interpersonal sexual communication and behaviors such as decreased condom use [54]. A history of trauma is not only associated with women's sexual health outcomes but is also associated with IPV [55].…”
Section: Summary Of Findingsmentioning
confidence: 74%
“…Women who have trauma history are over twice as likely to have multiple sex partners, perceive peer norms for risky sex, have lower communication frequency with partners about sexual boundaries, and have lower self-efficacy for refusing sex. This study adds to the literature showing that having a history of trauma may be associated with greater adverse interpersonal sexual communication and behaviors such as decreased condom use [54]. A history of trauma is not only associated with women's sexual health outcomes but is also associated with IPV [55].…”
Section: Summary Of Findingsmentioning
confidence: 74%
“…In one of the few studies that examined racial differences, black women experienced five times more childhood maltreatment than white women 20. Childhood sexual abuse increased adult risk for lifetime STI acquisition, along with partner concurrency, emotional trauma and lifetime sex trading in a sample of 66% black women 21. Among young women who used marijuana, black women were more likely to engage in high-risk sexual behaviours and progress to marijuana use than white women 22.…”
Section: Introductionmentioning
confidence: 97%
“…20 Childhood sexual abuse increased adult risk for lifetime STI acquisition, along with partner concurrency, emotional trauma and lifetime sex trading in a sample of 66% black women. 21 Among young women who used marijuana, black women were more likely to engage in high-risk sexual behaviours and progress to marijuana use than white women. 22 Previous research found that each additional ACE reported among black women was associated with a 49% increased risk of experiencing very early sexual initiation at 11–12 years old.…”
Section: Introductionmentioning
confidence: 99%
“…Many scientists investigating mental health found a higher prevalence of depression, anxiety, insomnia and violence in the population during the outbreak of COVID-19, concluding that the pandemic harmed the mental health of the population [15,16]. Reports from the literature suggest a link between women's quality of life, sexual health and stressful events in their life [17,18]. The evidence on the impact of the COVID-19 pandemic on sexual behavior is growing [19].…”
Section: Introductionmentioning
confidence: 99%